Art in Tanzania 2001. - Goscinny, Yves; Siege, Nasrin; East African Movies, Dar es Salaam; Alliance Française Dar-es-Salaam (Dar-es-Salaam : East African Movies, 2001)
Abdallah, Saidi ; Ailinda, Sawe ; Aloyce, Mayko ; Amonde, Omary ; Anagangola, Abumuwasi ; Bajaj, Amrit ; Barthals, Galus ; Bogaert, Pascal ; Bonda, Francis Pascal ; Bruno, Jeji ; Bushir Mruta, Salum ; Casmiro, Salvador ; Chagefe, Patricia ; Chamng'anda, Haji Ramadhan ; Charinda, Mohamed ; Chikawe, Evarist ; Chikoko, David ; Chilonga, Haji ; Chimwanda, Abdalla ; Chimwanda, Zaburi M. ; Chipenya, Godwin Jocktan ; Chiwaya, Rajabu ; Chuma, Salum A. ; Costales, Miguel ; Cyprian, Evance ; Dastani, Nyedi ; Dastani, Simuni ; Daudi, Doto ; Dula, Boute ; Emanuely, Jeremia ; Fadhili, Mohamed ; Flo, Montgomery ; Halla, Fred ; Hamedi, Abdul ; Hamedi, Athumani ; Hassani Kamale, Abdelehemani ; Hicks, Paul ; Hwago, Hussein ; Imanjama, Francis Patrick Lubas ; Jaffary, Magreth ; Jaffary, Rashid Aussi ; Jafferji, Javed ; Jengo, Elias ; Joakim, Adriano Mpuika ; Job, John Lulandala ; Joleka, Joseph Kateya Laizer ; Kalembo, Meshack Fidelis ; Kambi, Salum ; Karinto, Saviera ; Kashmiri ; Kenguru, Samuel Seth SiKenguru ; Kiiza, Gabriel Birungi ; Kilaka, John ; Kimvuli, Adam ; Kirita, Mary E. ; Kitogo, Ally ; Kyando, David ; Lambwende, Lucas Norbert ; Laurent, Véronique ; Leopard, Leopold Bonifas Livigha ; Lilanga, George ; Lilanga, Hemrick John ; Ludovick, Florian ; Lumbi, Kapompo ; Lutashobya, Emmanuel ; Lyombo, Joseph ; Magwamluhe, Mrisho J. ; Makuti, Antoni Chipanda ; Malaba, Agostino ; Malikita, Maulusi ; Malulu, Boniphace ; Mandawa, Doreen ; Mandengule, Selemani ; Mantheakis, Stella ; Manyanga, Mohamed ; Martin, Peter ; Masoud, Ali ; Matemu, Senator E.L. ; Matonya, Samuel ; Matunda, Anna Nestory ; Mawji-Patel, Ayesha ; Mbago, Rashid ; Mbalale ; Mbise, Eliaremisa Wilfred ; Mbunga, Saidi ; Mbwalela, Solomoni Vincent ; Mchalla, Bruno Paul ; Mcheni, Madhi ; Merinyo ; etc.
biog. per kunstenaar
Engels
Art in Tanzania 2001, Alliance Française Dar-es-Salaam / East African Movies Dar-es-Salaam, 30.11 - 22.12.2001
boek
Keywords: Tanzania